Import competition and household debt - Jean-Noël Barrot; Erik Loualiche; Matthew Plosser; Julien Sauvagnat (Federal Reserve Bank of New York, 2017)
We analyze the effect of import competition on household balance sheets from 2000 to 2007 using individual data on consumer finances. We exploit variation in exposure to foreign competition using industry-level shipping costs and initial differences in regions' industry specialization. We show that household debt increased significantly in regions where manufacturing industries are more exposed to import competition. A one standard deviation increase in exposure to import competition explains 30 percent of the cross-regional variation in household leverage growth, and is mostly driven by home equity extraction. Our results highlight the distributive effects of globalization and their consequences for household finances.
Keywords: D14; F6; G21; 330; trade; household finance; mortgages